Long-term effects of portuguese forest fires on morphology and aquatic habitat structure of lotic ecosystems - Vaz, Pedro Jorge Gonçalves (2014)
This thesis investigates long-term effects of forest fires on morphology and functioning of Portuguese streams via burned wood. Wildfires influenced the landscape dynamics across three regions examined, towards increases in shrublands encroaching into previously forested areas. Large wood amounts within 27 streams were low and are expected to decline in the future owing to wildfire. Likewise, wildfire was promoting wood lacking structural complexity, thus likely reducing habitat heterogeneity that improves conditions for aquatic organisms. The effect of fire providing wood with greater diameter will increase its probability for stream functions such as pool formation. However, this functionality may not persist because most of this wood was decayed and less stable in the channel. It is critical for aquatic communities if fire-derived wood falls directly into the river or if it is previously conditioned for some time on the forest floor; Efeitos a longo prazo dos fogos florestais na morfologia e estrutura do habitat em ecossistemas lóticos de Portugal ### Esta tese avalia os efeitos a longo prazo dos fogos florestais na morfologia e funcionamento de rios portugueses através da madeira ardida. O fogo influenciou a dinâmica da paisagem em três regiões estudadas, favorecendo a invasão por matos de áreas previamente florestadas. A quantidade de pedaços de madeira em 27 rios foi baixa e prevê-se a sua diminuição futura por influência do fogo. O fogo promoveu também a presença de madeira com menor complexidade estrutural, reduzindo provavelmente a heterogeneidade de habitat que melhora as condições para os organismos aquáticos. A madeira queimada tinha maior diâmetro, aumentando a probabilidade de função no rio, como a criação de fundões. Esta funcionalidade pode não persistir porque esta madeira estava degradada e menos estável no canal. É determinante para as comunidades aquáticas se a madeira dos fogos cai directamente no rio ou se é previamente condicionada durante algum tempo no solo da floresta.